2017
DOI: 10.18805/ijar.b-3285
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Mx gene polymorphisms in Indian native chicken breeds and White Leghorn by real time multiplex allele specific PCR

Abstract: Chicken Mx protein confers resistance against viral infections including avian influenza virus. Mx protein is one of the strong antiviral proteins induced by interferon system. Different alleles of chicken Mx gene have been shown to vary in their antiviral activity against influenza virus. A non-synonymous mutation at position 2032 of chicken Mx gene responsible for variation of amino acid (Ser to Asn) in Mx protein is responsible for negative to positive antiviral activity of Mx protein.In the present study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In contrast, the results in local breeds were more variable, which could be associated with the higher genetic diversity generally present in unselected breeds. Overall, the susceptible G allele prevails in the Spanish chickens tested, while the resistant A allele was the predominant in two Indian native chicken breeds [54], a native chicken breed from Indonesia [55] and 2 chicken breeds and 7 strains from Egypt [56]. The statistical analyses showed that the different genotypes in the target Mx region were not associated with significant differences in mortality ratios.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, the results in local breeds were more variable, which could be associated with the higher genetic diversity generally present in unselected breeds. Overall, the susceptible G allele prevails in the Spanish chickens tested, while the resistant A allele was the predominant in two Indian native chicken breeds [54], a native chicken breed from Indonesia [55] and 2 chicken breeds and 7 strains from Egypt [56]. The statistical analyses showed that the different genotypes in the target Mx region were not associated with significant differences in mortality ratios.…”
Section: Discussionmentioning
confidence: 90%
“…The genomic size of the chicken Mx gene is about 21 kbps with the coding sequences of about 2118 bps encoding the Mx protein comprising 705 amino acids [4, 5]. Like other IFN-response genes, the chicken Mx gene contains a sequence element in its promoters that serve as inducible enhancers.…”
Section: Introductionmentioning
confidence: 99%